The inverted mirror : mythologizing the enemy in France and Germany, 1898-1914 - Nolan, Michael E. (Studies in contemporary European history., 2005)
It is hard to imagine nowadays that, for many years, France and Germany considered each other as ""arch enemies."" And yet, for well over a century, these two countries waged verbal and ultimately violent wars against each other. This study explores a particularly virulent phase during which each of these two nations projected certain assumptions about national character onto the other - distorted images, motivated by antipathy, fear, and envy, which contributed to the growing hostility between the two countries in the years before the First World War. Most remarkably, as the author discovere